Cluster approach in the pedagogical research of future teachers - Begmatov Raximjon Raxmonqulovich (Peerian Journals Publishing, 2022)
The modern cluster system in education is aimed at the development of the individual and its maturity, and its interconnectedness is a chain of lifelong learning, which includes such processes as kindergarten, school, lyceum, college, university, doctorate, training.
Keywords: cluster; legal-educational; subject; object